Cultivating Global Competence Through Character and Citizenship Education in Singapore - Tan, Charlene; Abbas, Diwi (Comparative and International Education / Éducation comparée et internationale)

(untitled) (University of Western Ontario, 2024)
This paper examines the cultivation of global competence in Singapore schools through a compulsory programme known as Character and Citizenship Education (CCE). The syllabuses of CCE, information from selected school websites on CCE and relevant official documents were examined by mapping them with the Organisation for Economic Co-operation and Development’s conception of global competence. The results reveal a communitarian orientation that emphasizes social attachments, shared interests and communal goals. Specifically, the concept of global competence is framed and positioned as achieving collective well-being and valuing human dignity and diversity. The example of Singapore suggests the significance of communitarian underpinnings for global competence, thereby adding to the existing literature on the diverse formulations of the notion of global competence across education systems.